2010
DOI: 10.1039/c0jm00846j
|View full text |Cite
|
Sign up to set email alerts
|

Design of star-shaped molecular architectures based on carbazole and phosphine oxide moieties: towards amorphous bipolar hosts with high triplet energy for efficient blue electrophosphorescent devices

Abstract: With a carbazole moiety as the electron donor and a phosphine-oxide moiety as the electron acceptor, two novel star-shaped bipolar hosts, 4,4 0 ,4 00 -tri(N-carbazolyl)triphenylphosphine oxide (TCTP) and 3,6bis(diphenylphosphoryl)-9-(4 0 -(diphenylphosphoryl)phenyl)carbazole (TPCz), have been designed and synthesized. Their topology structure differences are that the phosphine-oxide moiety is located in the molecular centre and the periphery for TCTP and TPCz, respectively. The star-shaped architecture imparts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(86 citation statements)
references
References 29 publications
0
86
0
Order By: Relevance
“…Under thermal stress the NR profile began to change at 90 °C, which is above the reported bulk glass transition temperatures of CBP [25][26][27] and BCP, [28][29][30] but below that of TCTA. [31,32] Modeling showed that the change was consistent with the d-BCP layer beginning to diffuse into the emissive guest:host layer ( Figure 2). After stressing the film at 100 °C the d-BCP was found to have diffused throughout the Ir(ppy) 3 :CBP layer but not into the d-TCTA.…”
Section: Doi: 101002/adma201104029mentioning
confidence: 56%
“…Under thermal stress the NR profile began to change at 90 °C, which is above the reported bulk glass transition temperatures of CBP [25][26][27] and BCP, [28][29][30] but below that of TCTA. [31,32] Modeling showed that the change was consistent with the d-BCP layer beginning to diffuse into the emissive guest:host layer ( Figure 2). After stressing the film at 100 °C the d-BCP was found to have diffused throughout the Ir(ppy) 3 :CBP layer but not into the d-TCTA.…”
Section: Doi: 101002/adma201104029mentioning
confidence: 56%
“…31 Using an insulating heteroatom is also an efficient strategy to obtain high E T materials with short π-conjugated pathway. 39 HOMO/LUMO levels respectively lie at -5.25 eV/-1.67 eV, and the disrupted conjugation via phosphine-oxide linkage preserves a high E T of 3.03 eV. Thus, the electronic structure of the bipolar molecules is almost identical to those of the corresponding central core, which is a crucial point to avoid the decrease of E T .…”
mentioning
confidence: 94%
“…Here, TPCz stands for 3,6-bis(diphenylphosphoryl)-9-(4-(diphenylphosphoryl)phenyl)-9H-carbazole, which acts as a hole/exciton-blocking material, and was developed by our group. [ 32 ] The concentration of FIrpic varied from 2.5 wt% to 15 wt%; the best device performance was obtained with a dopant concentration of 5 wt% ( Figure 5 ). This device showed a turn-on voltage of 6 V, a maximum luminous effi ciency ( η l,max ) of 23. , the EQE still remained as high as 9.1%.…”
Section: Methodsmentioning
confidence: 99%